The Fed takes on corporate credit risk: An analysis of the efficacy of the SMCCF - Simon Gilchrist; Bin Wei; Vivian Z. Yue; Egon Zakrajések (Federal Reserve Bank of Atlanta, 2020)
We evaluate the efficacy of the Secondary Market Corporate Credit Facility (SMCCF), a program designed to stabilize the corporate bond market in the wake of the COVID-19 shock. The Fed announced the SMCCF on March 23 and expanded the program on April 9. Regression discontinuity estimates imply that these announcements reduced credit spreads on bonds eligible for purchase 70 basis points (bp). We refine this analysis by constructing a sample of bonds-issued by the same set of companies-that differ in their SMCCF eligibility. A diff-in-diff analysis shows that both announcements had large effects on credit spreads, narrowing spreads by 20 bp on eligible bonds relative to their ineligible counterparts within the same set of issuers across the two announcement periods. The March 23 announcement also reduced bid-ask spreads 10 bp within 10 days of the announcement. By lowering credit spreads and improving liquidity, the April 9 announcement had an especially pronounced effect on "fallen angels." The actual purchases lowered credit spreads by an additional 5 bp and bid-ask spreads by 2 bp. These results confirm that the SMCCF made it easier for companies to borrow in the corporate bond market.
Keywords: E44; E58; G12; G14; 330; COVID-19; credit market support facilities; regression discontinuity; diff-in-diff; event study; purchase effects